Usulan Perbaikan Proses Changeover Bagian Upper di PT XYZ Menggunakan Single Minute Exchange Of Die (SMED) - Susanto, Dani; Putra, Boy Isma (Journal of Research and Technology, 2024)
PT XYZ is a manufacturing company engaged in the production of leather shoes. In carrying out production activities, the company prioritizes quality production results and good productivity levels. The problem with the company was the high time set up changeover of the engine in the upper division. A change of engine is required to work on shoe products in this division. This current set up changeover caused the production process to be interrupted and timed out. The number of set up changeover times reaches 119.16 minutes for one set up changeover. This study aims to find out the factors that cause the changeover set up process and improve with the Single Minutes Exchange of Dies (SMED) method. Fishbone diagrams produce that long cause set up changeover due to method, human, machine and environmental factors. With the implementation of the SMED method, 25 internal activities were converted into 12 internal activities. This change resulted in an engine setup time of 119.16 minutes to 55.46 minutes and a 46.5% reduction in engine set up time.